Cash Swipe Spaylater: an Overview of Sharia Economic Law - Fidya Fitra Munjir Munjir; Irma Suriyani; Setiyo Utomo (Jurnal Mulawarman Law Review, 2025)
Spaylater cash swipe is the process of disbursing the SPaylater credit limit by manipulating transactions by making engineering orders. This practice of engineering Spaylater transactions can be called an illegal practice because it is contrary to shopee regulations and policies and misuses the true function of SPayLater. Where the credit limit on the Spaylater cannot be disbursed in the form of cash but can only be used to purchase goods or make payments through the installment method according to the terms and conditions stated in the Spaylater settings. In the perspective of Sharia Economic Law, Spaylater's cash swipe services are contrary to Islamic business law and sharia principles, where there are elements of gharar, mudharat, tadlis and injustice. This research uses socio-legal research by analyzing and studying the operation of law in society. This research uses data sources from primary data, secondary data, and tertiary data. The data obtained is done with data collection techniques through observation, interviews and documentation. By using the socio-legal research method, this research is expected to produce complete, valid, and in-depth findings or data to achieve the research objectives.The results showed that the transaction mechanism on cash swipe through Spaylater uses a checkout system, but does not receive real goods but only fictitious orders. Because it is considered contrary to Shopee's policy, the Civil Code, and is not in accordance with the principles of sharia, the legal consequences are that this practice is considered fasid and bathil because there is injustice, there is no good faith in the transaction, and there is no honesty. In addition, service providers and consumers can get consequences to the extent of sanctions that can be carried out by Shopee.